Recognition of emotion from facial expression in multiple sclerosis - Warwick, Ross (The University of Edinburgh, 2008)
(1) INTRODUCTION Multiple Sclerosis (MS) is a chronic, degenerative neurological condition. It is associated with a range of disabling physical, emotional, cognitive, and social sequelae. It has been demonstrated that people with MS are impaired relative to healthy controls at recognising emotion from facial expression and prosody. It has also been demonstrated that other neurological populations are impaired at recognising the emotional states of others. The present study aimed to further explore the relationship between MS and emotion recognition from facial expression and ascertain whether impaired recognition of emotion from facial expression was associated with reports of everyday social functioning.

(2) METHOD Thirty people with MS were assessed using the Facial Expression of Emotion: Stimuli and Tests, comprised of the Ekman 60 Faces and the Emotion Hexagon. Their performance was compared to the published normative data of the FEEST collected from neurologically healthy controls (n = 227; n = 125 respectively). Each MS participant was asked to complete a questionnaire about everyday functional behaviour, the Brock Adaptive Functioning Questionnaire. A parallel version was completed for each MS participant by a significant other.

(3) RESULTS

FEEST The MS group were significantly worse at overall recognition of emotion (p<.001; p<0.05). Using published cut-off scores, 36.67% of the MS group were classified as impaired on the Ekman 60 Faces; 23.33% on the Emotion Hexagon, significantly greater than the than the 5% expected from the normative data (/?<.001). There were also significant between-group differences on recognition of individual emotions.

BAFQ BAFQ informant reports of aggression were significantly correlated with recognition of disgust on both FEEST tests (p = .001). Although several other correlations were approaching significance, no other significant correlations (i.e. /?<.01) were found. Scores on the BAFQ were generally low, suggesting few social behaviour impairments in the current sample.

(4) DISCUSSION It was confirmed that people with MS have difficulty recognising emotion from facial expression but insufficient evidence was found to show that this was related to reported social behaviour. The implications for further research are discussed, along with a critique of the methodology.